SOCIO-PSYCHOLOGICAL TRAINING FOR ADOLESCENTS, AIMED AT PREVENTING AND OVERCOMING THE NEGATIVE MANIFESTATIONS OF LONELINESS EXPERIENCE - Diachok, Olga (International Journal of Innovative Technologies in Social Science, 2020)
The article is devoted to the theoretical and methodological study of the problem of experiencing loneliness in adolescence and empirical testing of the developed program of socio-psychological training to overcome and prevent the negative manifestations of loneliness. The purpose of the study was to test the effectiveness of the developed training, which was performed in three stages. At the ascertaining stage, the indicators of adolescents’ loneliness, level of satisfaction with certain aspects of school life, level of development of vitality, self-esteem and emotional abilities (empathy, expression and management of emotions, acceptance of responsibility for one’s emotions) were determined. At the formative stage, training was conducted with two groups of adolescents, each of which included 15 participants. At the control stage, the differences between the indicators of loneliness experienced by adolescents, the level of satisfaction with certain aspects of school life, the level of vitality, self-esteem and the level of development of emotional abilities before and after the study participants were tested. For the control group, the differences between the indicators of the first and second sections were also checked. The results of the formative stage of the study indicate the effectiveness of the implemented program of socio-psychological training for adolescents. Comparative analysis of the indicators of the first and second sections confirmed the positive changes in the experimental group after the training.